Inhibitory effect of the extract from Sonchus olearleu on the formation of carcinogenic heterocyclic aromatic amines during the pork cooking. (July 2019) - Teng, Hui; Chen, Yi; Lin, Xiujun; Lv, Qiyan; Chai, Tsun-Thai; Wong, Fai-Chu; Chen, Lei; Xiao, Jianbo
Abstract: The aim of this study was to assess the inhibitory effects of Sonchus olearleu extract on the generation of heterocyclic amines in roasted pork patties cooked by pan-frying. All samples were cooked for two different durations (45 min and 105 min) under 200 °C and 230 °C. 2-amino-3-methylimidazo[4, 5-f]quinoline (IQ), 2-ami- no-3, 8-dimethylimidazo[4, 5-f]quinoxaline (MeIQx), 2-amino-3, 4, 8-trimethylimidazo[4, 5-f]quinox-aline (4, 8-DiMeIQx), harman, and norharman were detected and quantified. In patties cooked at 230 °C for 105 min, S. olearleu extract (0.5%) significantly inhibited the formation of IQ, harman, and norharman by 39%, 67%, and 63%, respectively. In contrast to IQ, the levels of harman and norharman were significantly reduced by the extracts tested. However, no such effects were observed for MeIQx and 4, 8-DiMeIQx. Notably, the inhibitory effect on heterocyclic amines is significantly correlated with the antioxidant potential and total phenolic content of S. olearleu extract.